One-Pot Synthesis of 3,4-Dihydropyrimidin-2(1H)-ones Catalyzed by Chlorosulfonic Acid - Jin Tong-Shou; Zhao Ying; Liu Li-Bin; Li Tong-Shuang (E-Journal of Chemistry)
An efficient synthesis of 3,4-dihydropyrimidin-2-ones (DHPMs) from the aldehydes, β-ketoesters and urea in ethanol using chlorosulfonic acid as the catalyst is described. Compared with the classical Biginelli reaction conditions, this method has the advantage of excellent yields and short reaction time.